2018
DOI: 10.3329/sja.v15i2.35154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed rate and row spacing on grain yield of sorghum

Abstract: An experiment to investigate the effect of seed rate (5, 7.5, 10, 12.5 and 15 kg ha , number of grains per head and grain yield. Row spacing had non-significant effect on stem diameter, number of heads per plant and 1000-grain weight. Row spacing at 30 cm produced the highest number of plants m -2 and plant height. Plant height increased with increase in seed rate in all the row spacing. Stem diameter decreased with increase in the seed rate and row spacing. Narrow row spacing (30 cm) and low seeding rate (5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Snider et al (2012) stated remarkable reduction in yield by increasing seed rate. Gondal et al (2017) also reported significant and constant reduction in seed yield by increasing seed rate. The seed rate has a significant influence on all agronomic parameters.…”
Section: Resultsmentioning
confidence: 87%
“…Snider et al (2012) stated remarkable reduction in yield by increasing seed rate. Gondal et al (2017) also reported significant and constant reduction in seed yield by increasing seed rate. The seed rate has a significant influence on all agronomic parameters.…”
Section: Resultsmentioning
confidence: 87%
“…An increase in weight per plant of Sorgum-2011 was due to greater plant height, leaf area, and stem diameter. Similarly, Gondal et al(2017) showed significant differences among sorghum cultivars regarding weight per plant. Furthermore, Ayub et al(2010) found non-significant differences in plant dry weight among six sorghum varieties, while Afzal et al (2012) compared different sorghum cultivars.…”
Section: Discussionmentioning
confidence: 91%
“…These circumstances were presumably because the research area was a coastal area which contained a lot of sand, neither tillage nor notillage was different. The land has not been used used for 6 months, so the nutrients were available and there was no competition between sorghum plants even though the spacing was different [33,34]. Irwan et al [9] stated that a good spacing really depends on the level of soil fertility, soil cultivation, fertilization, and the varieties used.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in population of more than 150,000 plants per hectare tends to increase yields though it is not that large [32]. The spacing did not have a significant effect on the growth of sorghum, but the spacing had a significant effect on crop yields per plot [33]. Spacing of 50 cm x 30 cm (133,333 plants/ha) gave higher yields per plot of 4.30 tons/ha compared to the spacing of 75 cm x 25 cm (106,666 plants/ha) of 3.50 tons/ha [31].…”
Section: Introductionmentioning
confidence: 91%